Peran Artificial Intelligence dalam Meningkatkan Efektivitas Digital Marketing pada TikTok Shop di Semarang - Wicaksono, Gesang Bagas; Farida, Ida; Wismantoro, Yohan; Nuryanto, Imam (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study examines the role of Artificial Intelligence (AI) in enhancing customer satisfaction on TikTok Shop in Semarang, focusing on chatbot, content personalization, and usability. A quantitative survey of 125 TikTok Shop users was conducted and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that chatbot, content personalization, and usability have positive and significant effects on customer satisfaction, with chatbot as the most influential factor, followed by content personalization and usabilit. These findings highlight the importance of optimizing AI-based features, particularly chatbot performance, to improve service quality and customer satisfaction in social commerce platforms, and support the applicability of the Theory of Planned Behavior in AI-driven digital marketing contexts.